RUNOFF FARMING IN REDUCING RURAL POVERTY IN CHOLISTAN DESERT - Ahmad, Farooq (Sociedade & Natureza, 2008)
Abstract: The proposed study strives to provide an overall picture for establishing a relationship of indigenous rainwater harvesting technology and its impact in poverty alleviation. The topographic form and the soil characteristics of Cholistan is the best catchment area for rainwater harvesting. Different profiles point out that the area is very poorly drained, capable of generating maximum runoff after absorbing minimum water. Water intake characteristics of fine textured soils show that infiltration rate is low to very low. Findings show that there is direct relationship between water availability and poverty reduction. Study also sheds light on both strengths and limitations of the indigenous technology on reducing rural poverty and recommends using this technology along with modern water harvesting techniques.